2015
DOI: 10.1039/c5ra16340d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and analysis of a new bioorganic metallic material

Abstract: Biofouling on metal surfaces is one of the main reasons for increased ship drag. Many methods have already been used to reduce or remove it with moderate success. In this study, a synthetic peptide has been utilized to react with 304 stainless steel aiming to generate a bioorganic stainless steel using a facile technique. After the reaction, white matter was found on the surface of the treated stainless steel via SEM, whilst the nontreated stainless steel had none. Elemental analysis confirmed that excessive N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Biofouling caused great environmental penalty in many fields, more than $78 billion per year was cost due to medical devices contamination in USA, and the loss of ship and underwater facilities caused by biofouling is more than $50 billion per year in the world . Many studies illustrated surface contamination can be decreased by surface modification . Economic loss and human health issues associated to biofilm formation, which raise an urgent need for developing anti‐biofilm method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofouling caused great environmental penalty in many fields, more than $78 billion per year was cost due to medical devices contamination in USA, and the loss of ship and underwater facilities caused by biofouling is more than $50 billion per year in the world . Many studies illustrated surface contamination can be decreased by surface modification . Economic loss and human health issues associated to biofilm formation, which raise an urgent need for developing anti‐biofilm method.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many studies illustrated surface contamination can be decreased by surface modification. [7][8][9][10] Economic loss and human health issues associated to biofilm formation, 11,12 which raise an urgent need for developing anti-biofilm method.…”
Section: Introductionmentioning
confidence: 99%
“…Energy dispersive spectrometry can be used to collect the element information of materials . In this study, EDS detector was applied to detect the distribution of the elements nitrogen and sulfur on the peptide‐modified sample surface.…”
Section: Resultsmentioning
confidence: 99%
“…Biofouling organisms will be difficult to adhere or easy to detach on the materials surface to achieve antifouling if the surface energy is low or ultra‐low . A new bioorganic material with lower surface energy which yielded by an unknown reaction of peptides and metals has been reported . It revealed that a chemical reaction of the peptide coatings with metals occurred and changed the electronic state of the metal surface .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation